2014
DOI: 10.1007/s00284-014-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ralstonia solanacearum from Asymptomatic Tomato Plants, Irrigation Water, and Soil Through Non-selective Enrichment Medium with hrp Gene-Based Bio-PCR

Abstract: Bacterial wilt of tomato caused by Ralstonia solanacearum (Smith) Yabuuchi et al. (Microbiol Immunol 39:897-904, 1995) is a serious disease, which causes losses up to 60 % depending on environmental conditions, soil property, and cultivars. In present investigation, nucleotide sequences of virulence, hypersensitive response and pathogenicity (hrp) gene were used to design a pair of primer (Hrp_rs 2F: 5'-AGAGGTCGACGCGATACAGT-3' and Hrp_rs 2R: 5'-CATGAGCAAGGACGAAGTCA-3') for amplification of bacterial genome. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Standardization of PCR and real time PCR analysis could play an important role for detection R. solanacearum from the disease in the seeds planting material, soil and irrigation water, where the pathogen survives in low number ( Table 1). The bacterial pathogen causing wilt disease can be detected by using conventional PCR with detection level from 10 2 cfu/ ml (Singh et al, 2014a) to 10 5 cfu/ ml (Khakvar et al, 2008). PCR based methods for the detection of R. solanacearum are usually based on the amplification of ribosomal sequences (16S rRNA or ITS region) and other conserved genes of bacteria (Pastrick et al, 2002;Ranajn et al, 2016;Singh et al, 2014a;Weller et al, 2000).…”
Section: Polymerase Chain Reaction (Pcr) Based Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…Standardization of PCR and real time PCR analysis could play an important role for detection R. solanacearum from the disease in the seeds planting material, soil and irrigation water, where the pathogen survives in low number ( Table 1). The bacterial pathogen causing wilt disease can be detected by using conventional PCR with detection level from 10 2 cfu/ ml (Singh et al, 2014a) to 10 5 cfu/ ml (Khakvar et al, 2008). PCR based methods for the detection of R. solanacearum are usually based on the amplification of ribosomal sequences (16S rRNA or ITS region) and other conserved genes of bacteria (Pastrick et al, 2002;Ranajn et al, 2016;Singh et al, 2014a;Weller et al, 2000).…”
Section: Polymerase Chain Reaction (Pcr) Based Diagnosismentioning
confidence: 99%
“…The bacterial pathogen causing wilt disease can be detected by using conventional PCR with detection level from 10 2 cfu/ ml (Singh et al, 2014a) to 10 5 cfu/ ml (Khakvar et al, 2008). PCR based methods for the detection of R. solanacearum are usually based on the amplification of ribosomal sequences (16S rRNA or ITS region) and other conserved genes of bacteria (Pastrick et al, 2002;Ranajn et al, 2016;Singh et al, 2014a;Weller et al, 2000). Molecular based detection of R. solanacearum causing bacterial wilt of tomato, chilli, brinjal and potato has been done by using specific primers Y2 and OLII and it also distinguished R. solanacearum from other saprophytic bacteria grown on TTC medium (Singh et al, 2010(Singh et al, , 2014a.…”
Section: Polymerase Chain Reaction (Pcr) Based Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic analysis based on different molecular methods have shown that R. solanacearum is a highly heterogeneous group of bacteria probably belonging to several species [8][9][10] that cannot be taxonomically resolved by the race/biovar system. Genetic diversity of plant pathogenic bacteria including R. solanacearum has been reported to use different methods such as RAPD [11], PCR-RFLP of hrp gene [12], Rep-PCR [13] and multilocus sequence typing (MLST) sequencing [14]. The assessment of the genetic diversity of R. solanacearum employing restriction arrangement length polymorphism analysis resulted in the identification of two clusters of strains denoted divisions 1 (Asiaticum) and 2 (Americanum) [8][9][10] proposed a new hierarchical classification scheme to distinguish the genetic diversity within R. solanacearum species complex.…”
Section: Introductionmentioning
confidence: 99%